El proceso de reestructuración económica nacional y su impacto en el sistema regional: 1976-1981 - Apey Guzmán, Alfredo (Investigaciones Geográficas: Una mirada desde el sur, 1983)
ln recent years, some Latin American countries -like Chile- have been experimenting a deep shift away from the traditional development style: having created a strong role for state intervention in the economy, the traditional model -"desarrollista"- emphasized industrial development, expanding the internal market, import substitution, and control over foreign investment. Some countries, like the Chilean case, have largely replaced such a model with a drastically different development approach: the unfettered integration of the national economy into the international market of goods, services and capital. This aperture or internationalisation of the local economy is based on a neoclassical economic view of free trade, private sector development of comparative advantages and a reduced role for the public sector. If the neo-classical approach of development is considered, the exploitation of the country's major comparative advantages-natural resources and export agriculture- should induce to less concentrated patterns of development, bringing up regional specialisation and, once the regional productive infrastructure is developed, there will be a tendency towards the dispersion of population among the systems of regions. From a general perspective, nevertheless, the regional outcome of the current economic strategy seems to be characterised by a process of inter-regional differentiation in which the exports-oriented regions (mainly mining) become the only functional ones to the comparative advantages approach. That is to say, only two regions have shown a relative process of economic polarisation toward the exploitation of natural resources. The other regions, however, which have been historically associated to internal market activities have not properly reacted to the economic restructuring process through higher level of specialisation on export commodities. On the contrary, both the inter and intra regional analyses show that the regions have become increasingly less specialised in primary activities.